2022
DOI: 10.30872/atasi.v1i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Pengujian Kinerja Web Server Atas Penyedia Layanan Elastic Cloud Compute (EC2) Pada Amazon Web Services (AWS)

Abstract: Pembuatan Web Server yang tangguh dalam segi kehandalan, kecepatan maupun performa pada Web Server menjadi hal yang wajib dalam menangani semua permintaan user / visitor. Banyak pilihan server yang dapat dijadikan sebuah Web Server salah satunya Virtual Private Server (VPS). Virtual Private Server (VPS) adalah sebuah Server yang dibagi menjadi beberapa bagian yang mempunyai system operation sendiri. Provider VPS yang menjadi favorit dan sering menjadi rekomendasi pilihan layanan VPS adalah Amazon Web Services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…VPS merupakan jenis hosting di mana sumber dayanya berasal dari satu server fisik yang terbagi menjadi beberapa server virtual yang beroperasi seperti dedicated server . Sementara Cloud hosting menggunakan sumber daya dari beberapa server fisik terpusat yang bekerja secara bersamaan, sering kali dalam bentuk cluster (Fandy, 2022) ).…”
Section: Pendahuluanunclassified
“…VPS merupakan jenis hosting di mana sumber dayanya berasal dari satu server fisik yang terbagi menjadi beberapa server virtual yang beroperasi seperti dedicated server . Sementara Cloud hosting menggunakan sumber daya dari beberapa server fisik terpusat yang bekerja secara bersamaan, sering kali dalam bentuk cluster (Fandy, 2022) ).…”
Section: Pendahuluanunclassified
“…The collaboration between OpenAI and AWS offers an innovative approach that can potentially improve cybersecurity at all levels, from early threat detection to protecting critical infrastructure [7,8]. The combination of AI's data-generating power and the AWS cloud's scalability promises to revolutionize how organizations address cyber challenges in an ever-changing digital environment.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies that attempt to measure the quality provided by cloud computing services base, either based on analytical QoS parameters or comparisons between CSPs. For example, a study by Fandy et Al measured the network quality of a web server in AWS using the Apache Jmeter app, following the load balancing and HTTP packet request test [12]. The result of said study has shown that web servers that are built on top of the EC2 (Elastic Compute Cloud) service work comparatively better than other servers built using different AWS services.…”
Section: Introductionmentioning
confidence: 99%